2006
DOI: 10.1111/j.1744-7402.2006.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Tribology of Carbide‐Derived Carbon Films

Abstract: Carbide‐derived carbon (CDC) films are produced at atmospheric pressure on the surfaces of carbide‐based ceramic materials and coatings by a high‐temperature chlorination process. These nanoporous carbon films contain carbon nano‐onions and amorphous carbon, and may contain nanocrystalline diamond and graphite as well, depending on the synthesis conditions. The combination of such diverse carbon phases in one material or coating provides unique and potentially useful properties for a wide range of engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…During a hydrogen treatment, since the sample is at the elevated temperature, the water to react with the CDC to form carbon monoxide and hydrogen gas, as seen in equation [3].…”
Section: Hydrogen Treatmentmentioning
confidence: 99%
“…During a hydrogen treatment, since the sample is at the elevated temperature, the water to react with the CDC to form carbon monoxide and hydrogen gas, as seen in equation [3].…”
Section: Hydrogen Treatmentmentioning
confidence: 99%
“…Carbide-derived carbon (CDC) is a carbon material derived from a carbide precursor [19][20][21][22]. It has been previously reported that CDC has a tunable structure and excellent tribological properties [19,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Carbide-derived carbon (CDC) is a carbon material derived from a carbide precursor [19][20][21][22]. It has been previously reported that CDC has a tunable structure and excellent tribological properties [19,23,24]. Inspired by these findings, CDC started being considered as a surface modification technique to mimic tribolayer for hip implants, especially for Ti6Al4V.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the characteristics of low friction and high wear resistance, the tribological properties of CDC coatings should be improved to use under extreme conditions [7][8][9][10][11][12]. Carroll et al demonstrated that CDC coatings with an onion-like structure exhibited low friction in dry nitrogen [10].…”
Section: Introductionmentioning
confidence: 99%